2019
DOI: 10.1016/j.ekir.2018.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Renal Cortical Necrosis Is Associated With Atypical Hemolytic Uremic Syndrome in Developing Countries

Abstract: Introduction Pregnancy-related acute kidney injury is the most common cause of renal cortical necrosis (RCN). Atypical hemolytic uremic syndrome (aHUS) as a cause of RCN in pregnant/postpartum is underevaluated. In the current article, we describe a series of cases of pregnancy-related RCN. Methods All cases with acute kidney injury (AKI) in the setting of pregnancy and postpartum state were included. Diagnosis of RCN was made by contrast-enhanced computerized tomograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
(22 reference statements)
2
10
0
Order By: Relevance
“…Pr-AKI was not very common in young mothers as 43 (20%) mothers with Pr-AKI were in the age group up to 20 years. Similar figures 43 (23%) were observed in the age group (21)(22)(23)(24)(25)(26)(27)(28)(29)(30) years. An alarming rise was noted in mothers belonging to the 3 rd group (>30 years) as 124 (57.4 %) belonged to this age group.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Pr-AKI was not very common in young mothers as 43 (20%) mothers with Pr-AKI were in the age group up to 20 years. Similar figures 43 (23%) were observed in the age group (21)(22)(23)(24)(25)(26)(27)(28)(29)(30) years. An alarming rise was noted in mothers belonging to the 3 rd group (>30 years) as 124 (57.4 %) belonged to this age group.…”
Section: Resultssupporting
confidence: 80%
“…However, outcome figures varied widely in different studies which may be the result of different study designs, population sizes and variable definitions of AKI. [19][20][21][22][23][24] All literature of the world is unanimous on the fact that high morbidity and mortality is associated with Pr-AKI and this issue needs early recognition and prompt management.…”
Section: Discussionmentioning
confidence: 99%
“…In our study CN was due to puerperal sepsis (52%), PPH (22.9%), abruptio (20.83%), and TMA (4.1%). In a recent study by Ramachandran et al 31 32 developed AKI in early pregnancy and 40.35% in late pregnancy. 3,4 However, like in our study, most cases of PRAKI in recent studies are now seen to occur postpartum.…”
Section: Discussionmentioning
confidence: 91%
“…23 In our study 72% cases of PRAKI occurred postpartum. In a study in 1970s 31 Chugh et al reported a high maternal mortality (MM) of 30% in their study. 3,4 Maternal mortality has been variously reported in recent Indian studies from 5 to 25% as shown in Table 2.…”
Section: Discussionmentioning
confidence: 94%
“…Hypertensive disorders causing AKI can occur throughout the late second to third trimesters (27)(28)(29). As illustrated in Figure 2, the most commonly reported primary causes for PR-AKI are widespread, however these factors are often multifactorial, which can worsen the clinical scenario for the pregnant patient (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). PR-AKI of any etiology can be severe and in some cases can lead to ARF, or the need for renal transplantation, plasma exchange, dialysis or pharmacological treatment (3,44).…”
Section: Aki During Pregnancymentioning
confidence: 99%